Pengaruh Penambahan Zeolit Dalam Peningkatan Kinerja Filter Air Untuk Menurunkan Konsentrasi Amoniak Pada Pemeliharaan Ikan Mas (Cyprinus Carpio) - Silaban, Tio Fanta; Santoso, Limin; -, Suparmono (University of Lampung, 2012)
Common carp (Cyprinus carpio) is one of freshwater fish that growing very rapidly as a commercial fish. One of the factors that influence growth of common carp is water quality. Zeolite klinoptilolit were applied as filter in aquaculture water quality management. Zeolite was used to improve water quality, especially the consentration of ammonia. Zeolite works exploit the ability ion exchange of Na+ and K+, which is a cation that can be exchange serves to neutralize poisons in metabolism. The aim of this study are to know additional amount of zeolite that give the best result for decrease ammonia consentration at common carp culture. The experimental by used completely randomized design with 4 treatments.. The treatments were with addition zeolite of treatment B = 150 g; C= 300 g; D = 600 g, and treatment A without the zeolite addition. The results showed that the addition zeolite of 600 grams as a chemical water filter at common carp culture gave the best result for decrease ammonia concentration had a different effect on the concentration of ammonia was maintained for 60 days (P<0.05). However, the addition of zeolite as a water filter did not give different effects on absolute growth, daily growth rate, and survival of common carp (P>0,05).